Forecasting--an approach to the problems of the future. - Bestuzhev-Lada, Igor (International Social Science Journal, 1969)
The article presents an approach to problems of forecasting. Until recently there seemed to be no need to distinguish precisely between the different approaches to problems of the future covered by the terms forecasting, planning, programming, designing and control, and little attention was given to the matter. The main features of each were considered to be self-evident. Views vary on the interrelations between forecasting and planning. Some people regard forecasting as a process preceding planning proper, others, as a step beyond planning, relating to the more distant future, which cannot be directly planned. Others again, contrast forecasting as means of regulating spontaneous socio-economic processes under capitalism with planning, the only way of regulating a planned economy under socialism. In spite of the basic differences between socialist planning and capitalist attempts at planning, it must not be forgotten that in a capitalist economy, too, forecasting and planning are two different things. Forecasting as a phenomenon peculiar to capitalism cannot be automatically opposed to planning as a purely socialist phenomenon. In general, forecasting may be defined as a particular kind of approach to the problems of the future, a continuous process parallel to planning, programming, designing and control, the object of which is to improve the scientific standards of the latter. At present the least developed is sociological forecasting, which comprises demographic forecasts, ethnic forecasts and anthropological forecasts. Sociological forecasting is far behind economic forecasting because it is frequently treated as a subsidiary of latter.